(untitled) (Research, Society and Development, 2020)
The National Program for Improving Access and Quality of Basic Care (PMAQ) is a program for managers to evaluate the pattern of quality by primary health care teams that investigate efficiency and effectiveness (EE) in implementation of Federal Government programs. Thus, this article goals is investigate if there are EE indicators in PMAQ on state of Piauí. To do that was necessary analyze the indices demonstrating for PMAQ and after that identify possible difficulties in the execution of yhe program in the state of Piauí. The methodological used for data balysis were descriptive and analytical with quantitative and qualitative approach. The article is based on the history and characterization of the PMAQ. Thus, it was evidenced thai in practice, the program has reasonably brought significant contributions tho the basic health units in the state of Piauí.